Antioxidant Enzyme Levels Inversely Covary with Hearing Loss After Amikacin Treatment - Klemens, James J.; Meech, Robert P.; Hughes, Larry F.; Somani, Satu; Campbell, Kathleen C.M. (Journal of the American Academy of Audiology, 2003)
This study's purpose was to determine if a correlation exists between cochlear antioxidant activity changes and auditory function after induction of aminoglycoside (AG) ototoxicity. Two groups of five 250-350 g albino guinea pigs served as subjects. For 28 days, albino guinea pigs were administered either 200 mg/kg/day amikacin, or saline subcutaneously. Auditory brainstem response testing was performed prior to the first injection and again before sacrifice, 28 days later. Cochleae were harvested and superoxide dismutase, catalase, glutathione peroxidase, glutathione-S-transferase, glutathione reductase activities and malondialdehyde levels were measured. All antioxidant enzymes had significantly lower activity in the amikacin group (p ≤ 0.05) than in the control group. The difference in cochlear antioxidant enzyme activity between groups inversely correlated significantly with the change in ABR thresholds. The greatest correlation was for the high frequencies, which are most affected by aminoglycosides. This study demonstrates that antioxidant enzyme activity and amikacin-induced hearing loss significantly covary.
Keywords: Amikacin; aminoglycosides; antioxidants; hearing loss; ototoxicity